Emotion regulation among 4–6 year-old children and its association with their peer relationships in Jordan - Qashmer, Amani F. (Frontiers in Psychology, 2023)
Specific characteristics and competencies are required for maintaining peer relationships, and this study hypothesizes that emotion regulation is one of the competencies. The current study aimed to investigate the association between emotion regulation and peer relationships in 4–6-year-old children, and examine the sex differences among them. This study examined sex differences in peer relationships and the emotion regulation ability of children aged 4–6 years. The study sample comprised 300 children aged 4–6 years [170 girls (56.7%) and 130 boys (43.3%)] studying in kindergarten and first grade in Jordan. As part of data collection, questionnaires were distributed to teachers. The Emotion Regulation Scale (ERC) was used to measure emotion regulation, and the Social Competence and Behavior Evaluation (SCBE) scale, a subscale of the SCBE, was utilized to assess peer relationships. The results revealed a positive relationship between emotion regulation and positive poles of peer relationships (integrated, calm, and pro-social) and a significant negative relationship between emotional lability/negativity and positive poles of peer relationships. These results can be used to design intervention programs to reduce aggressive behavior in children.